2020
DOI: 10.1101/2020.02.18.955187
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adolescent Social Isolation Reprograms the Medial Amygdala: Transcriptome and Sex Differences in Reward

Abstract: Adolescence is a sensitive window for reward-and stress-associated behavior. Although stress during this period causes long-term changes in behavior in males, how females respond is relatively unknown. Here we show that social isolation stress in adolescence, but not adulthood, induces persistent but opposite effects on anxiety-and cocaine-related behaviors in male vs. female mice, and that these effects are reflected in transcriptional profiles within the adult medial amygdala (meA). By integrating differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 79 publications
0
8
1
Order By: Relevance
“…In these studies, we separated animals at PD 28, which is consistent with a well-established adolescent isolation paradigm commonly used in male rats (Butler et al, 2014a , 2016 ; Skelly et al, 2015 ). However, others have isolated animals earlier in adolescence; for example, Walker and colleagues separated C57BL/6J males and females from PD 22–42 and did not find that isolation during this period increased EPM open arm time (Walker et al, 2020 ). Given the rapid shifts in hormonal and neuroendocrine profiles across adolescence and puberty in rodents, slight differences in the onset of isolation could potentially have significant long-term behavioral implications (Walker et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, we separated animals at PD 28, which is consistent with a well-established adolescent isolation paradigm commonly used in male rats (Butler et al, 2014a , 2016 ; Skelly et al, 2015 ). However, others have isolated animals earlier in adolescence; for example, Walker and colleagues separated C57BL/6J males and females from PD 22–42 and did not find that isolation during this period increased EPM open arm time (Walker et al, 2020 ). Given the rapid shifts in hormonal and neuroendocrine profiles across adolescence and puberty in rodents, slight differences in the onset of isolation could potentially have significant long-term behavioral implications (Walker et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shown are the average + SEM levels of weekly alcohol intake per group. Post hoc pairwise comparisons: ** or *** significant difference between adolescent water and adolescent alcohol (p < 0.01 or p < 0.001, respectively); # significant difference between low and high playing rats (p < 0.05) play deprivation was shown to result in augmented cocaine and alcohol self-administration (Baarendse et al 2014;Lesscher et al 2015) and enhanced cocaine-, amphetamine-and alcohol-induced conditioned place preference in adulthood (Walker et al 2020;Whitaker et al 2013). Moreover, children who engage(d) more in outdoor play show improved self-regulation and conflict resolution skills (Tremblay et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, treatment with low doses of alcohol enhances social play behaviour in rats (Trezza et al 2009;Varlinskaya et al 2001Varlinskaya et al , 2010Varlinskaya and Spear 2002). Moreover, play deprivation in rats has been shown to result in enhanced sensitivity for cocaine selfadministration (Baarendse et al 2014) and for cocaine-, amphetamine-and alcohol-induced conditioned place preference (Walker et al 2020;Whitaker et al 2013). Also, play deprivation augmented alcohol consumption in adulthood (Lesscher et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the few studies investigating isolation in females found that SI-R has no effect on cocaine CPP at a low dose [2 mg/kg; ( 81 )]. However, this effect may be dose, species and/or isolation-type specific as others have shown that resocialization after aSI decreases preference for cocaine at a higher dose [7.5 mg/kg; ( 84 )] in mice. Similarly, SI-R increases preference for ethanol in male rats ( 79 ).…”
Section: Adolescent Social Isolation Stress Disrupts Adult Behaviormentioning
confidence: 99%
“…The key driver genes identified in the Walker et al ( 121 ) ranged in biological functions and display sex-specific expression across multiple treatments groups. A full list of key driver genes identified in the PFC, NAc and VTA is published in Walker et al ( 84 ). Overall, the authors observed a greater transcriptional response to acute and chronic cocaine in the NAc of aSI males but not females, with very little overlap in the cocaine-induced differentially expressed genes (DEGs).…”
Section: Adolescent Social Isolation Impacts On Dopaminergic Protein and Gene Expression In The Nacmentioning
confidence: 99%